ANALISIS PELEPASAN INFORMASI REKAM MEDIS KEPADA PIHAK KETIGA DI RS WAVA HUSADA: Analysis of the Release of Medical Records Information to Third Parties at Wava Husada Hospital - Afifah, Lilik; Duana, Farma; Anggraini, Fany (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
This study aims to examine the procedures for the release of medical records information to third parties at Wava Husada Hospital, ensuring compliance with applicable regulations to maintain the security and confidentiality of patient data. The research method used is a qualitative approach, including direct observation, in-depth interviews, and analysis of relevant documents. The results show that the procedure for releasing medical record information involves several important steps, including filling out an application form, submitting photocopies of official identification, and, if necessary, a notarized power of attorney. This process involves several related parties, such as the Medical Records Department, doctors or medical personnel, and ward staff working in inpatient or outpatient units. The main purposes for third-party requests for medical records information include insurance claims, transfer of treatment to ensure continuity of care, and administrative or consultation needs.